Central control over local government - a western European comparison - Goldsmith, Michael (2002)
This article reviews the way in which central government control over municipal government has changed across Western Europe over the last 30 years. Having outlined the different ways in which central governments can exercise control over local government both formally and informally, the article examines the changing experience in unitary, federal and quasi-federal countries in Western Europe. It also considers the impact on intergovernmental relations of the development of the European Union. The article concludes by suggesting that forms of central control have changed in recent years, involving a shift from direct control and intervention to more indirect control exercised through regulation. - Reproduced.
Keywords: Local government